2021
DOI: 10.20849/ijsn.v6i2.896
|View full text |Cite
|
Sign up to set email alerts
|

A Survey of Nurses’ Knowledge of and Attitudes Toward Hospitalized Older Adults

Abstract: Aim: To investigate the knowledge and attitudes of nurses towards older adults in the Taiwanese hospital.Design: A descriptive correctional study.Methods: A survey by random sampling of one teaching hospital for clinical nurses (N=80). The structural scales included demographic details, Palmore’s Facts on Aging Quiz (PFAQ) knowledge scale, and Kogan’s Old People (KOP) attitude scale. Lastly, we used Pearson’s correlation analyses to identify the correlates.Results: The rate of knowledge about aging was low at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 23 publications
2
0
0
Order By: Relevance
“…The finding was consistent with the studies in Bahir Dar Ethiopia (42.7%) (17) and west Shoa (37.2%) (13). This finding was lower than the previous studies conducted in Saudi Arabia (65%) (18), Taiwan Teaching Hospital (55.76%) (19), Israel (51%) (20), teaching hospital in Ghana (88.7%) (21), and study among critical care nurses in Egypt (79.8%) (22). This disparity could be attributed to difference, in study settings, as well as lack of training and formal education in the study area about geriatric nursing care.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The finding was consistent with the studies in Bahir Dar Ethiopia (42.7%) (17) and west Shoa (37.2%) (13). This finding was lower than the previous studies conducted in Saudi Arabia (65%) (18), Taiwan Teaching Hospital (55.76%) (19), Israel (51%) (20), teaching hospital in Ghana (88.7%) (21), and study among critical care nurses in Egypt (79.8%) (22). This disparity could be attributed to difference, in study settings, as well as lack of training and formal education in the study area about geriatric nursing care.…”
Section: Discussionsupporting
confidence: 90%
“…This study also found that Nurses having good knowledge about geriatric nursing care were three times more likely to have a positive attitude toward geriatric nursing care compared to nurses having poor knowledge about geriatric nursing care. This finding is supported by previous studies in Turkey (30), Israel (20), Taiwan (19), and Addis Ababa (11). This might be because nurses with good knowledge about geriatric care can better understand older people and their care which could contribute to having a positive attitude toward geriatric nursing care.…”
Section: Discussionsupporting
confidence: 90%